Chemical-shift imaging utilizing the positional shifts along the readout gradient direction. - Altbach, M.I.
Describes a method that uses the linear phase acquired during the readout period due to chemical shift to generate individual magnetic resonance (MR) images of chemically shifted species. The method utilizes sets of Fourier (or κ-space) data acquired with different directions of the readout gradient and a postprocessing algorithm to generate chemical shift images. The methodology is developed for both Cartesian data acquisition and for radial data acquisition. The method is presented here for two chemically shifted species but it can be extended to more species. Here, the authors present the theory, show the results in phantoms and in human images, and discuss the artifacts and signal-to-noise ratio of the images obtained with the technique.
Keywords: Cartesian data acquisition; Artifacts; Chemical-shift imaging; Human images; Magnetic resonance imaging; Medical diagnostic imaging; Phantoms; Positional shifts; Postprocessing algorithm; Radial data acquisition; Readout gradient direction; Signal-to-noise ratio